Step * 1 1 1 1 2 of Lemma partition-sum-bound-no-mc


1. Interval
2. icompact(I)
3. I ⟶ℝ
4. {b:ℝ(r0 ≤ b) ∧ (∀x:ℝ((x ∈ I)  (|f x| ≤ b)))} 
5. partition(I)
6. partition-choice(full-partition(I;p))
7. : ℕ||p|| 1 ⟶ {x:ℝx ∈ I} 
8. a ∈ (ℕ||p|| 1 ⟶ {x:ℝx ∈ I} )
9. ||full-partition(I;p)|| (||p|| 2) ∈ ℤ
10. : ℤ
11. 0 ≤ i
12. i ≤ (||full-partition(I;p)|| 2)
13. (full-partition(I;p)[i 1] full-partition(I;p)[i]) |full-partition(I;p)[i 1] full-partition(I;p)[i]|
⊢ (|f (a i)| |full-partition(I;p)[i 1] full-partition(I;p)[i]|) ≤ (b
(full-partition(I;p)[i 1] full-partition(I;p)[i]))
BY
(Assert ⌜|f (a i)| ≤ b⌝⋅ THENA Auto) }

1
.....assertion..... 
1. Interval
2. icompact(I)
3. I ⟶ℝ
4. {b:ℝ(r0 ≤ b) ∧ (∀x:ℝ((x ∈ I)  (|f x| ≤ b)))} 
5. partition(I)
6. partition-choice(full-partition(I;p))
7. : ℕ||p|| 1 ⟶ {x:ℝx ∈ I} 
8. a ∈ (ℕ||p|| 1 ⟶ {x:ℝx ∈ I} )
9. ||full-partition(I;p)|| (||p|| 2) ∈ ℤ
10. : ℤ
11. 0 ≤ i
12. i ≤ (||full-partition(I;p)|| 2)
13. (full-partition(I;p)[i 1] full-partition(I;p)[i]) |full-partition(I;p)[i 1] full-partition(I;p)[i]|
⊢ |f (a i)| ≤ b

2
1. Interval
2. icompact(I)
3. I ⟶ℝ
4. {b:ℝ(r0 ≤ b) ∧ (∀x:ℝ((x ∈ I)  (|f x| ≤ b)))} 
5. partition(I)
6. partition-choice(full-partition(I;p))
7. : ℕ||p|| 1 ⟶ {x:ℝx ∈ I} 
8. a ∈ (ℕ||p|| 1 ⟶ {x:ℝx ∈ I} )
9. ||full-partition(I;p)|| (||p|| 2) ∈ ℤ
10. : ℤ
11. 0 ≤ i
12. i ≤ (||full-partition(I;p)|| 2)
13. (full-partition(I;p)[i 1] full-partition(I;p)[i]) |full-partition(I;p)[i 1] full-partition(I;p)[i]|
14. |f (a i)| ≤ b
⊢ (|f (a i)| |full-partition(I;p)[i 1] full-partition(I;p)[i]|) ≤ (b
(full-partition(I;p)[i 1] full-partition(I;p)[i]))


Latex:


Latex:

1.  I  :  Interval
2.  icompact(I)
3.  f  :  I  {}\mrightarrow{}\mBbbR{}
4.  b  :  \{b:\mBbbR{}|  (r0  \mleq{}  b)  \mwedge{}  (\mforall{}x:\mBbbR{}.  ((x  \mmember{}  I)  {}\mRightarrow{}  (|f  x|  \mleq{}  b)))\} 
5.  p  :  partition(I)
6.  y  :  partition-choice(full-partition(I;p))
7.  a  :  \mBbbN{}||p||  +  1  {}\mrightarrow{}  \{x:\mBbbR{}|  x  \mmember{}  I\} 
8.  y  =  a
9.  ||full-partition(I;p)||  =  (||p||  +  2)
10.  i  :  \mBbbZ{}
11.  0  \mleq{}  i
12.  i  \mleq{}  (||full-partition(I;p)||  -  2)
13.  (full-partition(I;p)[i  +  1]  -  full-partition(I;p)[i])
=  |full-partition(I;p)[i  +  1]  -  full-partition(I;p)[i]|
\mvdash{}  (|f  (a  i)|  *  |full-partition(I;p)[i  +  1]  -  full-partition(I;p)[i]|)  \mleq{}  (b
*  (full-partition(I;p)[i  +  1]  -  full-partition(I;p)[i]))


By


Latex:
(Assert  \mkleeneopen{}|f  (a  i)|  \mleq{}  b\mkleeneclose{}\mcdot{}  THENA  Auto)




Home Index